Floating thrombus in the arch of the aorta: A diagnostic dilemma in coronavirus disease 2019 (Indian Journal of Case Reports, 2021)
Coronavirus disease 2019 (COVID-19) primarily involves the respiratory system, however, hypercoagulability and thromboembolism are its unique and common association. COVID-19 may predispose patients to an increased risk of thrombotic complications through various pathophysiologic mechanisms, such as inflammation, immobilization, endothelial dysfunction, and a hypercoagulable state. Therefore, a high index of clinical suspicion is needed for diagnosing thrombotic complications such as floating thrombus in the arch of the aorta as described in this case report and prompt anticoagulation should be started to prevent life-threatening complications. We describe a rare presentation of a patient who presented to intensive care unit of our hospital with respiratory symptoms and was being treated for COVID-19 and despite the management as per COVID protocol was difficult to wean off from the non-invasive ventilation. We will focus on how we arrived at this rare diagnosis “floating thrombus in the arch of aorta” and further management of the case.